Ultrahigh solar-driven atmospheric water production enabled by scalable rapid-cycling water harvester with vertically aligned nanocomposite sorbent. Issue 11 (12th October 2021) - Xu, Jiaxing; Li, Tingxian; Yan, Taisen; Wu, Si; Wu, Minqiang; Chao, Jingwei; Huo, Xiangyan; Wang, Pengfei; Wang, Ruzhu
Abstract : A rapid-cycling continuous solar-driven atmospheric water harvester, enabled by vertically aligned nanocomposite sorbent, was developed for realizing ultrahigh water production. Abstract : Freshwater scarcity is a globally significant challenge threatening the development of human society. Sorption-based atmospheric water harvesting offers an appealing way to solve this challenge by extracting clean water from the air. However, the weak ability of sorbents to capture water from dry air and the low water productivity of devices are two long-standing bottlenecks for realizing efficient atmospheric water harvesting. Here, we report a vertically aligned nanocomposite sorbent, LiCl@rGO–SA, by confining lithium chloride (LiCl) in a reduced graphene oxide (rGO) and sodium alginate (SA) matrix. The sorbent shows high water uptake, as high as thrice its weight, by integrating the chemisorption of LiCl, deliquescence of monohydrate LiCl·H2 O, and absorption of LiCl aqueous solution. Moreover, LiCl@rGO–SA exhibits fast sorption–desorption kinetics enabled by the vertically aligned and hierarchical pores of the rGO–SA matrix as water vapor transfer channels. We further engineered a scalable solar-driven rapid-cycling continuous atmospheric water harvester with synergetic heat and mass transfer enhancement. The water harvester using LiCl@rGO–SA realized eight continuous water capture-collection cycles per day and ultrahigh water productivity up to 2120 mLwater kgsorbent −1 day −1 from dry air without any other energy consumption. Our demonstration of the high-performance nanocomposite sorbent and scalable atmospheric water harvester offers a low-cost and promising strategy for efficiently extracting water from the air.